“Hide your sickness and put on a happy face”: The effects of supervision distrust, surface acting and sickness surface acting on hotel employees’ emotional exhaustion - Correia Leal, C.; Ferreira, A. I.; Carvalho, H. (Journal of Organizational Behavior, 2023)
The study of emotional labor and sickness presenteeism in the hotel industry is crucial due to the current context of economic uncertainty and to a climate of insecurity that forces employees to continue to show up for work even despite being sick. This research aimed to explore the effect of supervision distrust as an antecedent of surface acting on hotel service employees’ emotional exhaustion levels. Sickness surface acting – the voluntary effort to suppress illness symptoms or to fake a healthy health status – was introduced as a new construct to explain the relation between a perception of supervision distrust and emotional exhaustion. A total of 166 employees from Portuguese hotels completed a five-day diary survey. From these, 58 reported working while ill. The results showed that surface acting mediated the relationship between emotional exhaustion and supervision distrust. Further analysis with a subsample of 58 employees who reported frequency of sickness presenteeism revealed that for sick employees, sickness surface acting mediated the relationship between supervision distrust perception and emotional exhaustion. These findings bring the sickness surface acting construct to the sickness presenteeism literature, and highlight the importance of creating policies to reduce and manage the negative consequences of supervision distrust - a factor capable of promoting attendance and sickness presenteeism behaviors. They also inform human resources managers of the negative impacts of “service with a smile” and sickness presenteeism in the hotel industry.